2015
DOI: 10.1155/2015/643176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subject Age, Gender, and Arch Length on Attitudes of Syrian Dentists towards Shortened Dental Arches

Abstract: Objective. This study aimed to investigate the impact of subject age, gender, and arch length on dentists' attitudes towards unrestored shortened dental arches. Materials and Methods. 93 Syrian dentists were interviewed and presented with 24 scenarios for male and female subjects of different ages and shortened dental arches of varying length. Participants were asked to indicate on a standardized visual analogue scale how they would value the health of the mouth if the posterior space was left unrestored. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, some of the dentists who were unaware of the concept reported no need to replace the missing molars. This was in accordance with other studies from nighbouring Arab countires, which reported a decrease in dentists' inclination to replace missing posterior teeth as the age of the patient increased and the number of posterior teeth lost decreased [25, 26].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, some of the dentists who were unaware of the concept reported no need to replace the missing molars. This was in accordance with other studies from nighbouring Arab countires, which reported a decrease in dentists' inclination to replace missing posterior teeth as the age of the patient increased and the number of posterior teeth lost decreased [25, 26].…”
Section: Discussionsupporting
confidence: 92%